Implikasi Fluktuasi Suku Bunga dan Kurs Terhadap Iklim Investasi di Indonesia - Arif Fadila; Novi Permata Indah (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
AbstrakThis studyi aims to examine the iimpact of interest rate fluctuations measured by the interest rate and IDR/USD exchange rate on theiinvestment climatee in Indonesia. The investment climate in Indonesia is measured by theCompositee Stock Pricee Index (CSPI). The objects ini this studyi are the timee seriess data from the CSPI, the iinterest rateand the exchange rate of IDR/USD. The time series data that will be used as the object of research are time series data from January 2014 to August 2019. The aanalysis technique used iis multiple linearr regression analysis. The results showed that both theiinterest rate and the eexchange rate had note significant effect on changes in the valuee of the CSPI. The influencee of the interest rateand IDR/USD eexchange rates on the CSPI were -0.2133 and 0.92. These results indicate that an increase in the exchange rate of IDR/USD will increase the value of the CSPI, while an increasei in the interest rateswill decrease the valuee of the CSPI. The study also found that more than 60% off the Composites Stock Prices Index was influenced by the two macroeconomic factors studied. This can bee seen from the proportion of the variance off the effect of the interest rateand the exchange rates on the CSPI of61.4%.